Pengomposan Sederhana Limbah Organik Pertanian - Muh. Azhari; Fahruddin Arfianto; Pienyani Rosawanti; Hariyadi; Utin Winarni (BALE LITERASI, 2026)
The generation of organic waste resulting from human activities to meet needs continues to rise alongside population growth. This is directly proportional to the rising cost of living—encompassing primary, secondary, and tertiary needs alike. Activities aimed at meeting needs that generate organic waste as a by-product must be properly managed; doing so helps the environment by reducing pollutants that could otherwise degrade environmental quality, given that the environment has a finite capacity to break down the organic waste produced by humans, communities, and other living organisms—such as that originating from the agricultural sector. Organic waste from the agricultural sector includes vegetable scraps, fruit waste, and other forms of organic biomass. Recognizing this potential, students from Universitas Muhammadiyah Palangka Raya have engaged in processing organic waste through simple composting methods; this approach makes the processing of agricultural organic waste straightforward and offers the potential for repurposing the material, particularly within the agricultural sector. The steps involved in the activity include the collection of agricultural organic waste; preparation and shredding; pre-treatment via heating the organic material; enzyme application; the addition of microorganisms (fermentation); and finally, product harvesting and drying. Thus, simple composting of agricultural organic waste can serve as an alternative for protecting the environment against primary and secondary agricultural waste pollution—specifically biomass, leachate, and greenhouse gas emissions, as well as the degradation of environmental aesthetics.